Progressive posterior cortical dysfunction - Fábio Henrique de Gobbi Porto; Gislaine Cristina Lopes Machado; Lilian Schafirovits Morillo; Sonia Maria Dozzi Brucki (Dementia & Neuropsychologia)
Abstract Progressive posterior cortical dysfunction (PPCD) is an insidious syndrome characterized by prominent disorders of higher visual processing. It affects both dorsal (occipito-parietal) and ventral (occipito-temporal) pathways, disturbing visuospatial processing and visual recognition, respectively. We report a case of a 67-year-old woman presenting with progressive impairment of visual functions. Neurologic examination showed agraphia, alexia, hemispatial neglect (left side visual extinction), complete Balint's syndrome and visual agnosia. Magnetic resonance imaging showed circumscribed atrophy involving the bilateral parieto-occipital regions, slightly more predominant to the right . Our aim was to describe a case of this syndrome, to present a video showing the main abnormalities, and to discuss this unusual presentation of dementia. We believe this article can contribute by improving the recognition of PPCD.